Variation Among Promising Genotypes of Fenugreek (Trigonella foenun graecum Linn.) for Symbiotic Nitrogen Fixation - Sinha, Kihenjit; Ramakrishna, K (Annals of Arid Zone, 2016)
A study was conducted on eleven high yielding varieties of fenugreek, along with a local variety, to evaluate their symbiotic potential with five local Rhiwbium meliloti isolates under controlled conditions. Significant differences were observed among the host genotypes and rhizobial isolates in respect of six symbiotic traits studied on plants cultured for 33 days. Interaction between the host and rhizobia was also significant for all the traits. On the basis of plant nitrogen content, isolate FR 3 and FR 9 were found superior. Host genotype UM 117 was generally a superior symbiotic partner.